Inorganic nitrate and nitrite supplementation fails to improve skeletal muscle mitochondrial efficiency in mice and humans - Ntessalen, Maria (Am J Clin Nutr, 2020)
BACKGROUND: Inorganic nitrate, abundant in leafy green vegetables and beetroot, is thought to have protective health benefits. Adherence to a Mediterranean diet reduces the incidence and severity of coronary artery disease, whereas supplementation with nitrate can improve submaximal exercise performance. Once ingested, oral commensal bacteria may reduce nitrate to nitrite, which may subsequently be reduced to nitric oxide during conditions of hypoxia and in the presence of “nitrite reductases” such as heme- and molybdenum-containing enzymes. OBJECTIVE: We aimed to explore the putative effects of inorganic nitrate and nitrite on mitochondrial function in skeletal muscle. METHODS: Mice were subjected to a nitrate/nitrite-depleted diet for 2 wk, then supplemented with sodium nitrate, sodium nitrite, or sodium chloride (1 g/L) in drinking water ad libitum for 7 d before killing. Skeletal muscle mitochondrial function and expression of uncoupling protein (UCP) 3, ADP/ATP carrier protein (AAC) 1 and AAC2, and pyruvate dehydrogenase (PDH) were assessed by respirometry and Western blotting. Studies were also undertaken in human skeletal muscle biopsies from a cohort of coronary artery bypass graft patients treated with either sodium nitrite (30-min infusion of 10 μmol/min) or vehicle [0.9% (wt:vol) saline] 24 h before surgery. RESULTS: Neither sodium nitrate nor sodium nitrite supplementation altered mitochondrial coupling efficiency in murine skeletal muscle, and expression of UCP3, AAC1, or AAC2, and PDH phosphorylation status did not differ between the nitrite and saline groups. Similar results were observed in human samples. CONCLUSIONS: Sodium nitrite failed to improve mitochondrial metabolic efficiency, rendering this mechanism implausible for the purported exercise benefits of dietary nitrate supplementation. This trial was registered at clinicaltrials.gov as NCT04001283.